ROS scavenging and ion homeostasis is required for the adaptation of halophyte Karelinia caspia to high salinity - Li, Cui; Mur, Luis A.J.; Wang, Qinghai; Hou, Xincun; Zhao, Chunqiao; Chen, Zhimin; Wu, Juying; Guo, Qiang (Frontiers in Plant Science, 2022)
The halophyte Karelinia caspia has not only fodder and medical value but also can remediate saline-alkali soils. Our previous study showed that salt-secreting by salt glands is one of main adaptive strategies of K. caspia under high salinity. However, ROS scavenging, ion homeostasis, and photosynthetic characteristics responses to high salinity remain unclear in K. caspia. Here, physio-biochemical responses and gene expression associated with ROS scavenging and ions transport were tested in K. caspia subjected to 100–400 mM NaCl for 7 days. Results showed that both antioxidant enzymes (SOD, APX) activities and non-enzymatic antioxidants (chlorogenic acid, α-tocopherol, flavonoids, polyamines) contents were significantly enhanced, accompanied by up-regulating the related enzyme and non-enzymatic antioxidant synthesis gene (KcCu/Zn-SOD, KcAPX6, KcHCT, KcHPT1, Kcγ-TMT, KcF3H, KcSAMS and KcSMS) expression with increasing concentrations of NaCl. These responses are beneficial for removing excess ROS to maintain a stable level of H2O2 and O2− without lipid peroxidation in the K. caspia response to high salt. Meanwhile, up-regulating expression of KcSOS1/2/3, KcNHX1, and KcAVP was linked to Na+ compartmentalization into vacuoles or excretion through salt glands in K. caspia. Notably, salt can improve the function of PSII that facilitate net photosynthetic rates, which is helpful to growing normally in high saline. Overall, the findings suggested that ROS scavenging systems and Na+/K+ transport synergistically contributed to redox equilibrium, ion homeostasis, and the enhancement of PSII function, thereby conferring high salt tolerance.